2017
DOI: 10.19082/5914
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pterygium in Iran: a systematic review and meta-analysis study

Abstract: Background and aimPterygium is one of the most prevalent pathologies involving the cornea, which can lead to various vision signs and even reduction in eyesight. No accurate estimate has been reported about the prevalence of pterygium in Iran. Hence, this study aimed to determine the pterygium prevalence in Iran by meta-analysis method.MethodsSearching for data of the last eleven years (from 2004 to 2015) was conducted using the keywords of pterygium, eye, and Iran in International and domestic indexing servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
(7 reference statements)
0
4
1
Order By: Relevance
“…This finding is higher as compared to other community based studies done in a China (17.9%), (6.4%), and (11.75%) [4,30,31], Indonesia (10.00%) [32], Iran (9.4%), (1.3%), (11%), (13.11%), and (14.99%) [3,14,33,34], Central Myanmar (19.6%) [13], South Korea (8.8%) and (6.7%) [10,24], Malaya Singapore(12.3%) [35], India (13%) and (11.7%) [20,36], Northern Japan (4.4%) [37], Spain (5.9%) [38] and Kolla diba, Ethiopia (18.5%) [23]. The possible reason behind our high finding could be it is carried out in a hot, dry, and dusty environment with low latitude that might contribute to the occurrence of pterygium [39,40].…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…This finding is higher as compared to other community based studies done in a China (17.9%), (6.4%), and (11.75%) [4,30,31], Indonesia (10.00%) [32], Iran (9.4%), (1.3%), (11%), (13.11%), and (14.99%) [3,14,33,34], Central Myanmar (19.6%) [13], South Korea (8.8%) and (6.7%) [10,24], Malaya Singapore(12.3%) [35], India (13%) and (11.7%) [20,36], Northern Japan (4.4%) [37], Spain (5.9%) [38] and Kolla diba, Ethiopia (18.5%) [23]. The possible reason behind our high finding could be it is carried out in a hot, dry, and dusty environment with low latitude that might contribute to the occurrence of pterygium [39,40].…”
Section: Discussioncontrasting
confidence: 62%
“…A pterygium is a wing-shaped fibro-vascular growth of conjunctiva on the superficial cornea/conjunctiva and is an elastotic degeneration of conjunctival stroma mainly due to Ultraviolet(UV) light exposure [ 1 , 2 ]. It is one of the most common disorders of the cornea that degrades the visual performance of the eye [ 3 ]. The prevalence of pterygium varies from 1.1% to 53% globally in different environmental conditions [ 4 7 ] and in Ethiopia, it reaches from 8.8% to 38.7% [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This type of lesion was found to be more prevalent in males than in females, with a statistically significant p value of < 0.001, which was not found in any other category. Other studies have also reported a high prevalence of pterygia, with an unusually higher proportion in women than men [ 2 , 20 ]. We attribute this to climatic and environmental factors related to heat and sand in addition to our cultural lifestyle, where females tend to spend more time indoors, avoiding the risk factors for pterygia, contrary to the observed different lifestyles of women in Iran.…”
Section: Discussionmentioning
confidence: 95%
“…The prevalence of pterygium in Iran is about 11%, which is more common in men than women (7) The pterygium has different surgical approaches that vary depending on the method, recurrence rate and surgical results. The highest recurrence rate is related to Bare Sclera method and the lowest recurrence rate is related to Conjunctiva limbal autograft method (8).…”
Section: Introductionmentioning
confidence: 99%